Companion of the ACM/SPEC International Conference on Performance Engineering 2020
DOI: 10.1145/3375555.3384381
|View full text |Cite
|
Sign up to set email alerts
|

Beyond Microbenchmarks: The SPEC-RG Vision for a Comprehensive Serverless Benchmark

Abstract: Serverless computing services, such as Function-as-a-Service (FaaS), hold the attractive promise of a high level of abstraction and high performance, combined with the minimization of operational logic. Several large ecosystems of serverless platforms, both open-and closed-source, aim to realize this promise. Consequently, a lucrative market has emerged. However, the performance trade-offs of these systems are not well-understood. Moreover, it is exactly the high level of abstraction and the opaqueness of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…In serverless-specific field, Microsoft researchers characterize the serverless workloads on Azure Functions [46]. FunctionBench [37] and SPEC-RG Vision [51] propose serverless benchmark designs to reflect various aspects of serverless computing. Previous works also evaluate and compare how serverless applications behave on different platforms [23,30,39].…”
Section: Related Workmentioning
confidence: 99%
“…In serverless-specific field, Microsoft researchers characterize the serverless workloads on Azure Functions [46]. FunctionBench [37] and SPEC-RG Vision [51] propose serverless benchmark designs to reflect various aspects of serverless computing. Previous works also evaluate and compare how serverless applications behave on different platforms [23,30,39].…”
Section: Related Workmentioning
confidence: 99%
“…Although including a cost model in cloud benchmarking studies is considered good scientific practice [37], in existing benchmarking studies on FaaS [24,[38][39][40][41] and DSP [4,42,43], cost evaluations can mainly be found for cloud functions, where the pay-perexecution pricing model has presented a significant paradigm shift.…”
Section: Related Workmentioning
confidence: 99%
“…Although PanOpticon has similar goals as BeFaaS, it neither supports detailed drill-down analysis nor federated multi-provider setups. Van Eyk et al [31] develop a high-level architecture and state requirements for serverless benchmarking. Unfortunately their project still appears to be in a vision state.…”
Section: Related Workmentioning
confidence: 99%